The Community Health Worker (CHW) Common Indicators Project: Engaging CHWs in Measurement to Sustain the Profession - Rodela, Keara; Wiggins, Noelle; Maes, Kenneth; Campos-Dominguez, Teresa; Adewumi, Victoria; Jewell, Pennie; Mayfield-Johnson, Susan (Frontiers in Public Health, 2021)
Despite progress in documenting the outcomes of Community Health Worker interventions, the lack of standardized measures to assess CHW practice has made it difficult for programs to conduct reliable evaluations, and impossible to aggregate data across programs and regions, impeding commitment to sustainable, long-term financing of CHW programs. In addition, while CHWs have sometimes been involved as data collectors, they have seldom been engaged as full partners in all stages of evaluation and research. This manuscript details the current work being done by the CI Project, demonstrating how CHWs are able to contribute to the integrity, sustainability, and viability of CHW programs through the collaborative development and adoption of a set of common process and outcome constructs and indicators for CHW practice and CHW program implementation.